Influence of the preparation method on planar perovskite CH3NH3PbI3-xClx solar cell performance and hysteresis - Ivanova, Alesja; Lebedeva, Kristina; Roze, M.; Kaulachs, I.; Tokmakov, Andrey (De Gruyter Open Ltd, 2017)
Organometal halide perovskites are promising materials for lowcost, high-efficiency solar cells. The method of perovskite layer deposition and the interfacial layers play an important role in determining the efficiency of perovskite solar cells (PSCs). In the paper, we demonstrate inverted planar perovskite solar cells where perovskite layers are deposited by two-step modified interdiffusion and one-step methods. We also demonstrate how PSC parameters change by doping of charge transport layers (CTL). We used dimethylsupoxide (DMSO) as dopant for the hole transport layer (PEDOT:PSS) but for the electron transport layer [6,6]-phenyl C61 butyric acid methyl ester (PCBM)) we used N,N-dimethyl-N-octadecyl(3-aminopropyl)trimethoxysilyl chloride (DMOAP). The highest main PSC parameters (PCE, EQE, VOC) were obtained for cells prepared by the one-step method with fast crystallization and doped CTLs but higher fill factor (FF) and shunt resistance (Rsh) values were obtained for cells prepared by the two-step method with undoped CTLs.
The present research has been supported by the State Research Programme “LATENERGI” and National Research Programme “Multifunctional Materials and Composites, Photonics and Nanotechnology (IMIS2)”.
Keywords: inverted structure; mixed halide cells; perovskite solar cells; planar heterojunction; Research Subject Categories::NATURAL SCIENCES:Physics